Editorial JIFAM, Volume 5, Issue 2, August 2023 - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
This JIFAM 5 (Issue 2) August 2023 publishes papers related to infrastructures reliability to develop the sustainable asset management for infrastructures. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Journal can publish the Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the fifth volume (Issue 2).